Analysis of Intrinsic and Extrinsic Elements Novel Rain by Tere Liye - Jumriati Jumriati; Herawati Arief S (Universitas Muhammadiyah Enrekang, 2024)
This research aims to determine the intrinsic and extrinsic elements of the novel Rain by Tere Liye. This research focuses on intrinsic and extrinsic elements in the novel Rain by Tere Liye. This type of research is qualitative research, namely analyzing the form of description, not in the form of numbers or coefficients regarding the relationship between variables. The data source in this research is the novel Rain by Tere Liye, consisting of 315 things. Length 21 cm, width 34 cm, published by Gramedia main library Jakarta 2016. The data collection technique for this research is note-reading technique, considering that the object of study in this research is a text, namely the novel Rain by Tere Liye. The data analysis used in this research is content analysis or scientific methods for studying and drawing conclusions by utilizing text.The research results show thatThe intrinsic elements in the novel Rain by Tere Liye have a theme of romance, the plot used is a back and forth plot, setting of place, setting of time, namely day, morning and evening. The characters in this novel are Lail, Esok, Maryam, Elijah, Lail's mother, Lail's father, Tomorrow's mother, Queen Mother, Mayor's wife, Mayor and Claudia. The point of view in this novel is as he, she and the person's name. The language styles used in this novel are personification, contradiction and pleonasm. The message in this novel is to accept everything that God has given us and always be unyielding. The extrinsic element in this novel is the author's background. Thus, it can be concluded that this novel proves that the tools used are very sophisticated because this novel is set in the future which prioritizes practicality.